Unveiling the Sex-Dependant Roles of Pannexin 1 in Skeletal Muscle and its Influence in Duchenne Muscular Dystrophy - Freeman, Emily (Université d'Ottawa / University of Ottawa, 2023)
Skeletal muscle has a tremendous capacity to regenerate in healthy individuals. However, there is a dramatic impairment in regenerative potential in Duchenne muscular dystrophy (DMD) resulting in progressive muscle degeneration, weakness, and ultimately muscle wasting. Duchenne muscular dystrophy (DMD) is the most common lethal genetic disorder among children affecting every 1:3600-1:6000 male births. While it is known that DMD is caused by the loss of the structural protein dystrophin, the mechanisms that perpetuate the disease progression are poorly understood. Unfortunately, no cure exists for DMD and affected individuals succumb to the disease between the second and third decades of life, highlighting the importance of discovering new therapeutic strategies for DMD patients. Our laboratory has shown that expression of pannexin1 (Panx1 in rodent; PANX1 in human) is increased during myogenesis in vitro and muscle development and regeneration in vivo, while its levels are reduced in muscles from severely dystrophic mice. Here we demonstrated that loss of Panx1 in male mice reduces progenitor number and fusion, decreases muscle fiber size, and significantly impairs muscle strength. Notably, these effects were more prominent in male than in female mice demonstrating a sex-dependant role for Panx1 in skeletal muscle. Using cell lines isolated from muscles of healthy donors and dystrophic patients, we found that PANX1 channel function is reduced in DMD myoblast cell lines. To investigate how Panx1 dysregulation contributes to DMD, a dystrophic (mdx) mouse model that lacks Panx1 (Panx1⁻ᐟ⁻/mdx) was generated. Panx1⁻ᐟ⁻/mdx mice have significantly reduced lifespan, impaired muscle strength, decreased muscle stem cell population, and increased signs of myofiber specific damage. Like myoblasts from healthy male mice, Panx1 channel inhibition reduced mdx myoblast fusion. Interestingly, overexpressing PANX1 in patient derived DMD myoblast cell lines increased their differentiation and fusion, further suggesting that increased PANX1 protein levels may hold therapeutic benefits in dystrophic muscles. Overall, we demonstrate for the first time that Panx1 exerts sex-dependant roles in muscle maintenance regeneration, and strength. Furthermore, we found that absence of Panx1 exacerbates dystrophic features and significantly reduces the lifespan of dystrophic mice. Moreover, these findings suggest a potential therapeutic benefit of increasing Panx1 levels in the muscles of dystrophic patients.
Keywords: Pannexin 1; Duchenne Muscular Dystrophy; Skeletal Muscle